Abstract 13145: Mixed Digital Model of Care in Real-Time for Mexican Patients With Heart Failure - GUIZAR, CARLOS; Alvarez, Amada; JORDAN, ANTONIO; Mendez, Arturo; DE LA FUENTE MANCERA, JUAN CARLOS; BARANDA, FRANCISCO; RODRIGUEZ, DANYA; VELAZQUEZ, ARANTXA; Cacelin, Rafael; LOPEZ, NANCY; DALI, LUIS; ZURITA, THANIA; et al. (Circulation (New York, N.Y.), 2022)
Introduction Decompensated heart failure (DHF) is the main cause of cardiovascular hospitalization. During 1-year follow-up (FU), at least one rehospitalization occurred in 56.6% of patients with HF. In Mexico, HF places great burden on patients, caregivers, and healthcare systems. New strategies are essential for early diagnosis and treatment of DHF. HypothesisUse of a digital tool is effective for remote monitoring of patients with CHF to reduce the number of hospitalizations and/or unscheduled visits to the ER. MethodsA mixed digital model of HF (MDM-HF) care has been developed. It included an app in patient’s mobiles (CardioEnlace) that allowed real time monitoring of key parameters. These data were transferred into HF Unit portal and integrated into the patient's clinical file. CardioEnlace allowed detection of decompensation events through 1) alerts by patient′s text messages and 2) system alerts when variables were out of security limits on three or more consecutive days. If a patient showed signs of DHF, he/she was reached to provide medical instructions and/or scheduled an early appointment. ResultsMDM-HF care was deployed in July 2021. Up to date 131 patients have been included. The median of age is 58 years (interquartile range 47.5-65.5) and 77.1% were male. Cardiovascular risk factors (CVRF) frequencies are shown in Table 1. HF was secondary to ischemic condition in 44.5% of the patients. At least one hospitalization in the previous 2 years was reported in 73.5% of the subjects. Cardio Enlace parameters are shown in Fig 1. A blood pressure <140/90 mmHg was reported in 89.5% of patients and the average exercise time was 32 min/day. CardioEnlace alerts from January 2022 to date, were 82. Reasons are shown in Table 2. Adjustments to the treatment were done immediately and none of the patients had been hospitalized. DiscussionMDM-HF care model supports an early detection of DHF and monitorization of CVRF treatment which affect around 50% of the patients. Follow-up evaluations would allow to assess its impact on hospitalizations/emergency admissions. MDM-HF care model is part of the HF National Mexican Registry that will integrate data-driven solutions to reduce lead times from diagnosis to therapy adjustments and reduce the economic burden of DHF.